Petroleum refinery engineering - Nelson, Wilbur Lundine (New York : McGraw-Hill, 1958)
The purpose of the book was the introduction of the principles of chemical engineering to the petroleum refining industry. It also provides a survey of the industry's engineering practices.
Includes bibliographical references and index.
occ 16/01/2019
Loans
Keywords: Petroleum